11. International E-learning Specifications - Friesen, Norm; McGreal, Rory (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
A previous report in this series discussed the classification of online course delivery systems according to the Advanced Distributed Learning Partnerships (ADL), and the international standards accepted by the ADL. The standardisation of courseware in this manner is necessary for the development of inter-institutional course sharing and quality control. The present report gives further definitions of the criteria applied by international standards organisations, and lists the principal specifications/ standards bodies now in operation.